Baptism as a criterion for acquiring the procedural role of a petitioner in catholic courts - Dobrotiuk, Ivan (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
This article examines the acquisition of the procedural role of a petitioner in Catholic tribunals through the prism of the Sacrament of Baptism. Therefore, the main legislative provisions that interpret the issue of access to the dimension of Catholic justice are analyzed here. The study clarifies the mechanism for determining the validity of baptism of persons belonging to dubious church communities, as well as those belonging to sects that consider themselves Christians. In addition, a comparative characteristic of the legislation of the Eastern Catholic Churches and the Latin Church regarding the aspect of the Sacrament of Baptism as a condition for the possibility of appearing before a Catholic judge as a petitioner is carried out here. Special attention is paid to the main elements that conceptually influenced the process of codification of the legislation of the Eastern Catholic Churches on the issue of access of non-Catholics to Catholic tribunals. As a result of the study, the main principle that guides modern procedural Catholic law, and therefore the place of non-Catholics in the canonical process, is clarified and highlighted. Basically, the prescriptions of Catholic law are designed for and bind only Catholics. Canon law explicitly states that the faithful of Catholic Churches can assert and defend their rights precisely before a competent Catholic tribunal if such a right has been violated or unjustly restricted. Therefore, since it concerns the internal life of the faithful of Catholic Churches, the question arises: can it be affirmed that baptism is the criterion by which canon law determines a person’s capacity to acquire the procedural role of a petitioner? After all, modern Catholic canon law in certain cases still regulates relations between Catholics and baptized non-Catholics (e.g., mixed marriages, communicatio in sacris, etc.) or between Catholics and unbaptized persons (e.g., dispensation from the impediment of disparity of cult, marital separation, etc.). Thus, if in such individual cases Catholics can deal with non-Catholics, do baptized non-Catholics or unbaptized persons participate in the sphere of Catholic jurisdiction? More precisely, is the absence of baptism an absolute impediment to acquiring the legal capacity to sue in a Catholic court? The purpose of the article is to analyze the provisions of modern legislation of the Catholic Churches for the presence of regulations regarding the role of the Sacrament of Baptism in the dimension of ecclesiastical justice, and mainly for the initiation of a canonical process, i.e., whether baptism is the ultimate criterion for a person to acquire the procedural role of a petitioner and appear before a Catholic judge. The material presented in the article allows us to state that the legislator of the Eastern Catholic Churches and the Latin Church does not use the presence of valid baptism as an absolute criterion and condition for acquiring the procedural role of a petitioner in a Catholic tribunal. It is obvious that a Catholic has a wider range of rights that he can protect in a competent court. However, we have seen that canonical procedural law goes very far beyond the boundaries of confessional affiliation. Thus, the Catholic legislator indeed applies the principle of justice, allowing non-Catholics, baptized and unbaptized, to appeal to a Catholic court when there is a corresponding reason for it. In this vein, Catholic procedural law does not distinguish between the baptized and the unbaptized, or between a member of one of the Catholic Churches and a baptized non-Catholic. In the context of the canonical process, it is important for the legislator to have a legal relationship with the Catholic Church, because it is precisely legal relations that become a potential support, relying on which a non-Catholic will be able to acquire the procedural role of a petitioner, observing, of course, other necessary conditions that a person must meet in order to have the right and ability to appear in court.